Targeted VEGF (Vascular Endothelial Growth Factor) Therapy Induces Long-Term Renal Recovery in Chronic Kidney Disease via Macrophage Polarization. Issue 5 (November 2019) - Engel, Jason E.; Williams, Erika; Williams, Maxx L.; Bidwell, Gene L.; Chade, Alejandro R.
Abstract : Chronic kidney disease (CKD) universally associates with renal microvascular rarefaction and inflammation, but whether a link exists between these 2 processes is unclear. We designed a therapeutic construct of VEGF (vascular endothelial growth factor) fused to an ELP (elastin-like polypeptide) carrier and show that it improves renal function in experimental renovascular disease. We test the hypothesis that ELP-VEGF therapy will improve CKD, and that recovery will be driven by decreasing microvascular rarefaction partly via modulation of macrophage phenotype and inflammation. CKD was induced in 14 pigs, which were observed for 14 weeks. At 6 weeks, renal blood flow and filtration were quantified using multidetector computed tomography, and then pigs received single intrarenal ELP-VEGF or placebo (n=7 each). Renal function was quantified again 4 and 8 weeks later. Pigs were euthanized and renal microvascular density, angiogenic and inflammatory markers, fibrosis, macrophage infiltration, and phenotype were quantified. Loss of renal hemodynamics in CKD was progressively recovered by ELP-VEGF therapy, accompanied by improved renal microvascular density, fibrosis, and expression of inflammatory mediators. Although renal macrophage infiltration was similar in both CKD groups, ELP-VEGF therapy distinctly shifted their phenotype from proinflammatory M1 to VEGF-expressing M2. Our study unravels potential mechanisms and feasibility of a new strategy to offset progression of CKD using drug-delivery technologies. The results indicate that renal recovery after ELP-VEGF therapy was largely driven by modulation of renal macrophages toward VEGF-expressing M2 phenotype, restoring VEGF signaling and sustaining improvement of renal function and microvascular integrity in CKD. Abstract : Supplemental Digital Content is available in the text.